Keanekaragaman serangga parasitoid (Ordo: Hymenoptera) pada areal persawahan dan kebun sayur - Manap Trianto; Varsha Salsabillah (Universitas Muhammadiyah Prof. Dr. Hamka, 2021)
Background: The Hymenoptera Order is one of the most dominant orders in the insect class, both in number of species and in their distribution in various habitats. The role of the Hymenoptera Order, especially parasitoids, is very important in a habitat. The purpose of this study was to determine the diversity of parasitoid insects, especially the order Hymenoptera in rice fields and vegetable gardens. Methods: This research is analytic descriptive. The research method used is a line transect using a sampling technique. The study was conducted in two research areas (rice fields and vegetable gardens) and used three fishing gears (malaise traps, buckets, and insect nets). Results: The results showed that the total number of insects caught was 5037 individuals from 10 orders and 80 family. The diversity of parasitoid insects in this study is in the rice fields H' = 1.80 (moderate diversity) and vegetable gardens H' = 2.26 (moderate diversity). Conclusions: Hymenoptera parasitoid insect diversity was highest in the vegetable garden area.